Green Taxation for SMEs' Digital Transformation of Accounting - Lemos, Kátia (2023)
The dematerialization of documents and the resulting contribution to greener and more sustainable practices should be on the agenda of businesses. Companies, especially SMEs, need to be particularly aware of the relevance of digitalization for environmental sustainability, and the role of governments in promoting the digitalization of companies is very important for its success. The present research focuses on the study of tax incentives for the digital transformation of accounting granted to Portuguese micro and SMEs, specifically for the implementation of SAF-T (PT) for accounting, the QR Code®, and the ATCUD. An exploratory data analysis methodology was adopted, considering all Portuguese micro and SMEs that participated in the tax incentive for digital transformation in 2020 and 2021. The authors conclude that the tax incentives studied have not been a practice adopted by Portuguese micro and SMEs, which may reveal a lack of disclosure by the government and knowledge by companies.